(untitled) (Hong Kong, 1988)
This is the first English edition of a major analysis of the economic geography of China: its abundant natural resources, systems of production, problems in economic development, and changes since the founding of the People's Republic of China in 1949.
Keywords: Trung Quốc,China; Điều kiện kinh tế,Economic conditions; 1949-,1949-